Geriatric depression among the retired elders in Madurai, Tamil Nadu, India - Meenakshi, J Raja (Indian Journal of Community Health, 2018)
Background: Retirement makes an impact on the psychological health of elders. Geriatric depression is common among elders and it is a major public health challenge in India. Aims & Objectives: To assess the level of Geriatric depression and its relationship with socio demographic factors. Materials and Methods: 5 retired associations out of 36 associations located in Madurai district were selected by simple random sampling which has the total members of 1934.As the stratum varies in each association, 64 respondents are selected from each association irrespective of the number of samples by adopting stratified disproportionate sampling method on the basis of the Krejice and Morgan (1970) sample table. Socio demographic details were collected with questionnaire and Geriatric depression was assessed with Geriatric Depression rating scale. Results: 28.1 per cent have medium level and 9.1 per cent have high level of Geriatric depression. Female has high level of geriatric depression when compared to male. Conclusion: Socio demographic factors of retired elders have a major impact on Geriatric depression and it has to be dealt as public health issue.